Discovery and Analysis of Documentation Systems and Medical Record Service Procedures at Hospital Nacional Guido Valadares - Anabela Markes; Alberto Alberto; Tita Hariyanti (Jurnal Penelitian Pendidikan IPA, 2023)
Prepare information to facilitate the service process to patients and facilitate managerial decision making by clinical and administrative service providers in hospitals. This study aims to identify problems, root causes, carry out identification of alternative solutions, develop programs as selected solutions, and intervention plans to improve the causes of documentation systems and procedures for medical record services at Hospital Nacional Guido Valadares. This research is qualitative research. The subjects of the study were representatives of section heads and unit heads, representatives of medical record officers. Data collection is observation, interviews, documentation, recorder, Focus Group Discussion (FGD), Urgency Serousness Growth (USG) and brainstorming. Results of root cause identification using fishbone diagram and 5 why's analysis, alternative solutions using FMEA, risk priority number (RPN). The result of this study is that the officer provides medical record documents belonging to patients taken home, new patients do not bring referral letters from doctors, do not bring Electoral cards or other identity cards. Old patients forget to bring their identity cards for treatment, come back not according to the doctor's appointment. Suggestions for socialization efforts continue to be carried out to educate, remind patients and officers about the documentation and procedures that have been established and periodic evaluations.